Synthesis of specific identified, phosphorylated, heat shock, and heat stroke proteins through the cell cycle of Saccharomyces cerevisiae. - Ludwig, J R (1982)
The methods of centrifugal elutriation, two-dimensional gel electrophoresis, and dual isotopic labeling were applied to the study and identification of a number of purified yeast proteins. The location of polypeptide spots corresponding to specific proteins was determined on two-dimensional gels. A dual-label method was used to determine the rates of synthesis through the cell cycle of the identified proteins as well as to confirm the results of previous studies from our laboratory on unidentified proteins. The identified proteins, and the more generally defined phosphorylated, heat shock, and heat stroke proteins were found to follow the general pattern of exponential increase in rate of synthesis through the cell cycle. In addition, colorimetric enzyme activity assays were used to examine the catabolic enzyme alpha-glucosidase (EC 3.2.1.20). Both the activity and synthesis of alpha-glucosidase were found to be nonperiodic with respect to the cell cycle. These data contrast with earlier reports of periodicity, which employed induction and selection synchrony to study enzyme expression through the yeast cell cycle.